Interaksi Antara Metode dan Tujuan Da'wah: Menilai Signifikansinya dalam Perubahan Perilaku Spiritual Manusia dari Perspektif Psikologi Islam - Sukataman, Sukataman; Santono, Agung Nugroho Reformis; Ulva, Maria; Thoha, Choliliyah (IAINU Kebumen, 2025)
This research is motivated by the phenomenon of dissonance between rigid da'wah methods and sublime spiritual goals, which often fails to produce authentic behavioral changes. This study aims to analyze the significance of the interaction between da'wah methods (wasīlah) and goals (ghāyah) in fostering human spiritual behavior change through the lens of Islamic psychology. This study employs a qualitative-descriptive method with a library research approach. Data were collected through academic literature documentation and analyzed using a thematic-integrative technique connecting da'wah theory with Islamic psychological concepts. The results indicate that spiritual transformation requires the internalization of values (internalized faith) through the mechanism of tazkiyat al-nafs, which harmonizes the structures of nafs, ‘aql, and qalb. Specifically, the formulation of Quranic methods—ḥikmah, mau‘iẓah ḥasanah, and mujādalah—serves as an adaptive response to the diversity of the audience's psychological conditions. The study concludes that da'wah must shift from an instructional paradigm toward a transformative-humanistic approach, particularly in the digital era, to foster autonomous consciousness and address the spiritual crisis of modern society.